Antibiotic Resistance in Staphylococcus aureus and Coagulase Negative Staphylococci Isolated from Goats with Subclinical Mastitis - Virdis, Salvatore (SAGE-Hindawi Access to Research, 2010)
Antimicrobial resistance patterns and gene coding for methicillin resistance (mecA) were determined in 25 S. aureus and 75 Coagulase Negative Staphylococci (CNS) strains isolates from half-udder milk samples collected from goats with subclinical mastitis. Fourteen (56.0%) S. aureus and thirty-one (41.3%) CNS isolates were resistant to one or more antimicrobial agents. S. aureus showed the highest resistance rate against kanamycin (28.0%), oxytetracycline (16.0%), and ampicillin (12.0%). The CNS tested were more frequently resistant to ampicillin (36.0%) and kanamycin (6.7%). Multiple antimicrobial resistance was observed in eight isolates, and one Staphylococcus epidermidis was found to be resistant to six antibiotics. The mecA gene was not found in any of the tested isolates. Single resistance against β-lactamics or aminoglicosides is the most common trait observed while multiresistance is less frequent.